Depression, Anxiety and Sleep Alterations in Caregivers of Persons With Dementia After 1-Year of COVID-19 Pandemic - Bussè, Cinzia; Barnini, Teresa; Zucca, Milena; Rainero, Innocenzo; Mozzetta, Stefano; Zangrossi, Andrea; Cagnin, Annachiara (Frontiers in Psychiatry, 2022)
Background: Social isolation due to Covid-19 pandemic has an important psychological impact particularly in persons with dementia and their informal caregivers. Aim: To assess frequency and severity of long-term stress-related symptoms in caregivers of patients with dementia one-year after the beginning of Covid-19 pandemic and to identify predictors of psychological outcomes. Methods: Eighty-five caregivers took part in a longitudinal study with one-year follow-up during pandemic in Italy. At baseline in April 2020 a telephone interview assessed socio-demographic characteristics of caregivers and self-perception of distress symptoms. After one year, between March and April 2021, the same standardized interview was delivered to the caregivers’ sample. In addition, scales assessing levels of depression and anxiety (DASS-21), sleep disturbances (PSQI) and coping strategies (COPE-NVI) were administered to the caregivers and to 50 age and sex-matched non-caregivers subjects. Linear regression analysis was performed to investigate the power of baseline variables to predict long-term psychological outcomes. Results: After one year of pandemic frequency of caregivers’ stress-related symptoms increased respect to baseline: depression (60% versus 5,9%; p< .001), anxiety (45,9% versus 29,4%; p= .035), irritability (49,4% versus 24,7%; p< .001), and anguish (31,7% versus 10,6%; p< .001). Frequency of severe depression was higher in caregivers than in non-caregivers (p=.002) although mean levels of depression were comparable in the two groups. Long-term higher depression was predicted by a model built on baseline information (r2=.53, p<.001) where being female (t=-3.61, p<.001), having lower education (t=-2.15, p=.04), presence of feelings of overwhelm (t=2.29, p=.02) and isolation (t=2.12, p=.04) were significant predictors. Female sex was also predictive of anxiety (t= -2.7, p=.01) and poor sleep quality (t= -2.17, p= .03) one year later. Discussion: At one year follow-up caregivers of patients with dementia reported higher prevalence of all stress-related symptoms respect to the acute phase of lockdown, particularly depression. Long-lasting stressful conditions may cause exhaustion of resilience factors and increased depression. Planning interventions should support caregivers to enable them to continue with their role during pandemic.